The sustained effect of 5-week EmotionCore mindfulness training on emotion regulation and emotional intelligence: heterogeneous benefits for depression and anxiety across subgroups - Kou, Hui; Luo, Wei; Wang, Yiwei; Wu, Jia; Li, Xiaodong; Wu, Yi; Xiao, Qianguo; Bi, Taiyong (Frontiers in Psychiatry, 2025)
BackgroundThe present study investigated the sustained effects of a 5-week EmotionCore mindfulness training program on emotion regulation, emotional intelligence (EI), trait mindfulness, depression, and anxiety among 120 undergraduates, while exploring the mediating mechanisms of training effect and heterogeneous effects across subgroups.MethodsParticipants were randomly assigned to a mindfulness group (n=60) or a waitlist control group (n=60), with assessments conducted at baseline (T1), post-training (T2), and one-month follow-up (T3).ResultsResults demonstrated that mindfulness training significantly enhanced adaptive cognitive emotion regulation strategies (ACERSs), EI, and trait mindfulness at both T2 and T3. Both cross-section and longitudinal mediation models revealed that improvements in ACERSs and EI fully and sequentially mediated the relationship between mindfulness training and trait mindfulness enhancement. Latent Profile Analysis revealed that the high-risk group (high baseline anxiety/depression) exhibited greater reductions in anxiety and depression at T2 and T3 compared to the low-risk group.ConclusionThese findings suggest EmotionCore mindfulness training fosters trait mindfulness through improvements in ACERSs and EI, and its targeted efficacy is specifically notable within high-risk populations.